2014
DOI: 10.1038/srep04914
|View full text |Cite
|
Sign up to set email alerts
|

Berberine exposure triggers developmental effects on planarian regeneration

Abstract: The mechanisms of action underlying the pharmacological properties of the natural alkaloid berberine still need investigation. Planarian regeneration is instrumental in deciphering developmental responses following drug exposure. Here we report the effects of berberine on regeneration in the planarian Dugesia japonica. Our findings demonstrate that this compound perturbs the regenerative pattern. By real-time PCR screening for the effects of berberine exposure on gene expression, we identified alterations in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 59 publications
0
24
0
Order By: Relevance
“…While other groups have normalized by the area of the worm (Balestrini et al. ; Kustov et al. ), we found that normalizing by the square of the worm's width was the most accurate way to account for size variation (Hagstrom et al.…”
Section: Neuroregeneration and Neurotoxicologymentioning
confidence: 74%
See 4 more Smart Citations
“…While other groups have normalized by the area of the worm (Balestrini et al. ; Kustov et al. ), we found that normalizing by the square of the worm's width was the most accurate way to account for size variation (Hagstrom et al.…”
Section: Neuroregeneration and Neurotoxicologymentioning
confidence: 74%
“…), and substances with unclear toxicity such as the natural alkaloid berberine (Balestrini et al. ) or silver nanoparticles (Kustov et al. ).…”
Section: Neuroregeneration and Neurotoxicologymentioning
confidence: 99%
See 3 more Smart Citations